Effective Hydrological Events in an Evolving Mid‐latitude Mountain River System Following Cataclysmic Disturbance—A Saga of Multiple Influences. Issue 2 (8th February 2021) - Major, J. J.; Spicer, K. R.; Mosbrucker, A. R.
Abstract: Cataclysmic eruption of Mount St. Helens (USA) in 1980 reset 30 km of upper North Fork Toutle River (NFTR) valley to a zero‐state fluvial condition. Consequently, a new channel system evolved. Initially, a range of streamflows eroded channels (tens of meters incision, hundreds of meters widening) and transported immense sediment loads. Now, single, large‐magnitude, or multiple moderate‐magnitude events are needed to accomplish substantial channel modification. Three large floods (two ≥100‐year events; one ∼10–25‐year event along lower Toutle River) from 1996 to 2015 indicate flood effectiveness in this environment is affected by both geomorphic and environmental factors. The largest and smallest of these floods (February 1996, November 2006) transported the most sediment by single floods since 1982; erosion and sediment transport by an ∼100‐year flood in December 2015 was not exceptional. Strong coupling between NFTR and its tall corridor banks, local geologic and hydraulic conditions promoting threshold erosion, event sequencing, and possibly a longitudinal gradient in stream power are important factors affecting event effectiveness on channel modification. In addition, environmental factors have also been influential, as variations in snowpack, storm trajectories and rainfall distributions, and episodic mobilization of debris flows have also influenced geomorphic response. Other factors such as vegetation anchoring, strong channel–hillside coupling, disparities between flood frequencies and perturbation relaxation times, and large variations in flood duration do not appear to be critical influences. Climate forecasts for warmer temperatures and a shift from snowfall to rainfall at high elevations may promote further acute geomorphic responses. Key Points: Three large floods affected an evolving, cataclysmically disturbed river system over a 20‐year span and produced varied geomorphic responses Event responses were influenced by storm character, snowpack cover, geomorphic process, and local hydraulic and geologic conditions Single, large‐magnitude, or multiple moderate‐magnitude events are currently needed to accomplish substantial channel modification